Hepatic damage exacerbates cisplatin-induced acute kidney injury in Sprague-Dawley rats. Issue 11 (3rd June 2018) - Kim, Ji Su; Son, Ji Yeon; Kim, Kyeong Seok; Lim, Hyun Jung; Ahn, Mee-Young; Kwack, Seung Jun; Kim, Young-Mi; Lee, Kwang Youl; Lee, Jaewon; Lee, Byung Mu; Kim, Hyung Sik
ABSTRACT: The objective of this study was to elucidate the effect of hepatic damage on cisplatin (CDDP)-induced acute kidney injury (AKI). Thioacetamide (TAA, 150 mg/kg), a hepatotoxicant, was intraperitoneally (i.p.) injected to male Sprague-Dawley rats for 3 d prior to CDDP (5 mg/kg, i.p.) injection. All animals were sacrificed 5 d after CDDP treatment, and urine or blood was obtained to measure various parameters. No significant changes in serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity were observed after CDDP treatment. However, pretreatment with TAA significantly elevated ALT and AST activity. Serum blood urea nitrogen and creatinine levels significantly increased in CDDP-treated group compared to control. In addition, urinary excretion of novel protein-based biomarkers such as neutrophil gelatinase-associated lipocalin, vascular endothelial growth factor, kidney injury molecule-1, and tissue inhibitor of metalloproteinase-1 rose markedly in the CDDP-treated group. In particular, pretreatment with TAA markedly elevated CDDP-induced urinary excretion of protein-based nephrotoxic biomarkers compared with CDDP alone. Hematoxylin and eosin staining demonstrated that pretreatment with TAA following CDDP injection led to more severe tubular damage and apoptosis in rats compared with CDDP alone. Antioxidant status was significantly reduced in kidneys following pretreatment with TAA prior to CDDP. These findings indicate that liver injury enhanced the vulnerability of kidney to CDDP-induced AKI and this phenomenon may be associated with severe apoptotic damage.